2017
DOI: 10.1038/nchem.2706
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic ion transporter that disrupts autophagy and induces apoptosis by perturbing cellular chloride concentrations

Abstract: Perturbations in cellular chloride concentrations can affect cellular pH and autophagy and lead to the onset of apoptosis. With this in mind, synthetic ion transporters have been used to disturb cellular ion homeostasis and thereby induce cell death; however, it is not clear whether synthetic ion transporters can also be used to disrupt autophagy. Here, we show that squaramide-based ion transporters enhance the transport of chloride anions in liposomal models and promote sodium chloride influx into the cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
216
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 224 publications
(227 citation statements)
references
References 56 publications
9
216
0
2
Order By: Relevance
“…1i : Squaramide 1i was prepared in (716 mg, 0.67 mmol, 67 % yield) as a white solid by following the procedure for the preparation of 1g . 1 H NMR and 13 C NMR spectra were in agreement with the previously reported spectrum: IR (neat) 3232, 1788, 1675, 1602, 1429, 1371, 1278, 1123, 935, 880; 1 H NMR (600 MHz, [D 6 ]DMSO) δ H = 10.15 (br, 3H), 7.85 (s, 6H), 7.51 (br, 3H), 7.39 (s, 3H), 3.73 (m, 6H), 2.82 (m, 6H); 13 C NMR (151 MHz, [D 6 ]DMSO) δ C = 185.1, 179.9, 169.5, 162.3, 140.9, 131.1 (q, J = 33 Hz), 123.0 (q, J = 273 Hz), 117.5, 114.4, 53.2, 41.8; HRMS (ESI) calcd. for C 40 H 27 F 18 N 7 O 6 [M + H] + : 1068.1769, found: m/z 1068.1801.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…1i : Squaramide 1i was prepared in (716 mg, 0.67 mmol, 67 % yield) as a white solid by following the procedure for the preparation of 1g . 1 H NMR and 13 C NMR spectra were in agreement with the previously reported spectrum: IR (neat) 3232, 1788, 1675, 1602, 1429, 1371, 1278, 1123, 935, 880; 1 H NMR (600 MHz, [D 6 ]DMSO) δ H = 10.15 (br, 3H), 7.85 (s, 6H), 7.51 (br, 3H), 7.39 (s, 3H), 3.73 (m, 6H), 2.82 (m, 6H); 13 C NMR (151 MHz, [D 6 ]DMSO) δ C = 185.1, 179.9, 169.5, 162.3, 140.9, 131.1 (q, J = 33 Hz), 123.0 (q, J = 273 Hz), 117.5, 114.4, 53.2, 41.8; HRMS (ESI) calcd. for C 40 H 27 F 18 N 7 O 6 [M + H] + : 1068.1769, found: m/z 1068.1801.…”
Section: Methodssupporting
confidence: 90%
“…The white residue was recrystallized from chloroform to give 1‐(3,5‐bis(trifluoromethyl)phenyl)‐3‐cyclohexylthiourea 1f as a white solid (735 mg, 1.98 mmol, 99 % yield). 1 H NMR and 13 CNMR spectra were in agreement with the previously reported spectrum: 1 H NMR (600 MHz, [D 6 ]DMSO): δ H = 7.42 (s, 1H), 7.29 (s, 2H), 6.82 (s, 1H), 5.19 (s, 1H), 4.40 (m, 1H), 1.91–0.86 (m, 10H); 13 C NMR (151 MHz, [D 6 ]DMSO): δ C = 179.2, 142.0, 130.1 (q, J = 33 Hz), 123.3 (q, J = 273 Hz), 121.8, 115.9, 52.3, 31.6, 25.1, 24.4.…”
Section: Methodssupporting
confidence: 88%
“…Next, to determine if PZ‐6‐QN promotes cancer cell death via the apoptotic process, HeLa cells were incubated with PZ‐6‐QN and then treated with a mixture of fluorescein‐annexin V and propidium iodide (PI). The results of flow cytometry analysis revealed that the cells exhibit positive annexin V binding and positive PI uptake after treatment with PZ‐6‐QN (Figure A), phenomena that are characteristic of apoptosis . It was also found that the size of cells decreases after treatment with PZ‐6‐QN (Figure S12A), thus providing additional evidence that PZ‐6‐QN has the apoptosis‐inducing ability .…”
Section: Resultsmentioning
confidence: 83%
“…For instance, a strapped calix[4]pyrrole transported Cl − across cell membranes effectively in the presence of functioning Na + channels and to induce apoptotic activity in several cancer cell lines (e.g., lung A549 and HeLa) [22]. Many other effective transporters are known and very recently one acted as an inhibitor of autophagy [23]. Several classes of anion transporters have been the subject of separate reviews [24,25].…”
Section: Introductionmentioning
confidence: 99%